From lichens to crops: Pathogenic potential of Pseudomonas syringae from Peltigera lichens is similar to worldwide epidemic strains - Ramírez, Natalia; Caullireau, Emma; Sigurbjörnsdóttir, Margrét Auður; Vandelle, Elodie; Vilhelmsson, Oddur; Morris, Cindy (Plant Pathology, 2024)
International audience The presence of bacteria belonging to the Pseudomonas syringae complex in the natural vegetation of several Icelandic habitat types has been recently reported, raising questions about the risk to Icelandic crops, particularly given the expected increase in agricultural activity due to climate warming. This study takes advantage of Iceland's unique characteristics and the discovery of P . syringae in Peltigera lichens to gain a better understanding of the potential risk posed by this newly discovered ecological niche. The main objective was to evaluate the pathogenic potential and fitness in crops of P . syringae strains isolated from Peltigera lichen sampled in Iceland, focusing on strains that belong to phylogroups 1 and 2, which commonly contain epidemic strains. The results indicate that P . syringae strains isolated from Icelandic Peltigera lichen have a comparable fitness to epidemic strains in 8 out of 10 tested plant species (rice, tomato, thale cress, annual mugwort, spinach, garlic chives, tobacco and kale). Furthermore, pathogenicity assessment on three plant species highlighted that certain strains also caused similar symptoms and disease severity compared to epidemic strains. These findings provide valuable insights into the potential risks posed by P . syringae from Icelandic natural habitats and illustrate how strains from these habitats have a wide pathogenic potential to crops without having encountered these crops in the last several thousand years of their presence in Iceland.